Chinese culture and its influence on female prisoner behavior in the prisoner–guard relationship - Liu, Liu (The Australian and New Zealand journal of criminology, 2018)
Although scholars have shown continuing interest in studying prisoner behavior, relatively few studies focus on Chinese female prisoners’ behavior in the prisoner-guard relationship. In this study, 65 semi-structured interviews were conducted with both female prisoners and guards to document Chinese culture’s influence on female prisoners’ behavior. According to the findings, female prisoners mainly choose to maintain good guanxi (interpersonal relationships) with guards, in order to pragmatically maximize the benefits of these relationships. In addition to this, based on personalism and pragmatism, they usually act in an individualistic manner, instead of forming prisoner sub-cultures. These findings suggest that Chinese female prisoners use multiple strategies to manage their relationships with guards, tending to employ methods centered on the notion of guanxi.